The Music of the zarzuela-sarsuwela a brief study of the etymology, character and significance of a Filipino expressive genre - Santos, Ramon Pagayon (2015)
The sarsuwela is a type of performing art which is based on a play and is performed with dialogue, music, and other stage elements of a musical theater. Although the entire form of the sarsuwela is in great part musical, most of the studies that have been done by Filipino researchers and writers in art studies and social sciences focus on the sarsuwela as part of the vernacular literature, or dealing with the importance of the sarsuwela as part of the history of Philippine society and culture. It is therefore the intention of the present study to give sufficient attention to the music of the zarzuela/sarsuwela, its artistic character, from its conceptual formation, its influences from other cultures, and its transfer and development in the Philippines. The discussion includes the birth of the zarzuela itself in Spain, the influences it acquired from other cultures, most especially in Italy, until t obtained its romantic form that was introduced in the Philippines, It is also within the interest of this present study to point out observations on the possible connection of the music of the sarsuwela to the creation of a type of repertory of Filipino songs that came ionto being and [proliferated during the last decade of the nineteenth century until the first decades of the twentieth century, becoming the parents of the art song such as the kundiman, as well as the modern Filipino popular song.
Keywords: Zarzuela; Musical theater; Theater -- Philippines -- History